Native language interference in learning english as foringn langauge: an analysis of written material produced by spanish speaking studets in senior high school classes. - Poma, Soraya (2010)
The topic analyzed throughout this research is “native language interference in learning english as a foreign language: an analysis of wWritten material produced by spanish speaking students in Senior High School Classes”.Nowadays in this globalized world the use of english language is necessary in different fields, especially to communicate with people from other cultures, for this reason the interaction of students in the classroom and outside of it should be carried on in a continuous way. Therefore, the aim of teachers is to have learners to master the target language, for this reason; we came up with the necessity to investigate how interference generates errors in written material.